Moderate Hypofractionated Post-Prostatectomy Radiotherapy (MYSTERY) Versus Conventionally Fractionated Post-Prostatectomy Radiotherapy (COPORT) for the Patients With Localized Prostate Cancer: The Protocol of a Prospective, Randomized Trial - Yiyin Liang MD; Weiwei Zhang MD; Xianzhi Zhao MD; Huojun Zhang MD, PhD (Cancer Control)
Introduction A few studies have examined whether the safety and efficacy of moderate hypofractionated post-prostatectomy radiotherapy (moderate HYPORT, also called MYSTERY) are equal to those of conventionally fractionated post-prostatectomy radiotherapy (COPORT) in patients with localized prostate cancer. Therefore, this study aims to compare the safety and efficacy of MYSTERY and COPORT in patients with postoperative prostate cancer. Methods and analysis This study is a prospective, single-center, open-label, randomized controlled clinical trial. Patients with localized prostate cancer will be randomly allocated to receive COPORT (66-74 Gy at 2 Gy per fraction) or MYSTERY (57.5-65 Gy at 2.5 Gy per fraction). The primary outcomes are radiotherapy-related gastrointestinal and genitourinary adverse events. Secondary outcomes include progression-free survival, quality of life, medical expenses, and overall survival.